Schools and Staffing Survey, 1990-1991: (United States) ([Verlag nicht ermittelbar], 1995)
This data collection consists of four integrated surveys of public and private schools, administrators, and teachers in the United States. Part 1, the Teacher Demand and Shortage Survey, presents information from schools and local education agencies on student enrollment, number of teachers, position vacancies, new hires, teacher salaries and incentives, and hiring and retirement policies. Part 3, the School Administrator Survey, includes information about training, experience, professional background, and job activities of school principals and headmasters. Questions in Part 5, the Teacher Survey, cover teacher education and training, teaching assignment, teaching experience, certification, teaching workload, perceptions and attitudes about teaching, job mobility, and workplace conditions. Part 7, the School Survey, provides data from elementary and secondary schools on student characteristics, staffing patterns, student-teacher ratios, enrollment by grade, types of programs and services offered, length of school day and school year, graduation and college application rates, and teacher turnover rates.